Computational insight into structural basis of human ELOVL1 inhibition. (May 2023) - Siddiqui, Arif Jamal; Kumar, Vikash; Jahan, Sadaf; Alshahrani, Mohammed Merae; Al Awadh, Ahmed Abdullah; Siddiqui, Maqsood Ahmed; Hamadou, Walid Sabri; Abdelgadir, Abdelmushin; Saxena, Juhi; Badraoui, Riadh; Snoussi, Mejdi; Adnan, Mohd
Abstract: Very long-chain fatty acids (VLCFAs) play a direct role in the development of a neurological disorder, X-linked adrenoleukodystrophy (X-ALD). Since ELOVL1 catalyzes the rate-limiting step of the synthesis of VLCFAs, it has emerged as an attractive target for the treatment of X-ALD. Recently two potent inhibitors, compound 22 (C22) and compound 27 (C27) have been reported to specifically inhibit human ELOVL1 but their structural basis of inhibition has not been explored. In the present study, we have used a homology model of human ELOVL1 to deduce the binding site and binding modes of C22 and C27. We have employed computational approaches to characterize the binding of C22 and C27. Initially, binding of hexacosanoyl-CoA (C26:0-CoA) to ELOVL1 was modelled and further validated by molecular dynamics (MD) simulation. We observed that the fatty acid tail of C26: CoA protrudes from a unique opening located at the occluded end of ELOVL1. Structural comparison of ELOVL1 with the crystal structure of ELOVL7 revealed that the unique opening was not present in human ELOVL7. Combined blind and focused molecular docking approaches revealed that C22 and C27 exhibit favourable binding in the same unique opening. Further, MD simulations and free binding energy calculations confirmed that C22 and C27 maintain the favourable binding in the unique opening of ELOVL1. Overall, our findings suggest that selective human ELOVL1 inhibitors block the binding of long tails of VLCFAs near the occluded end of ELOVL1. Present study will be helpful in the discovery and design of novel, selective and potent inhibitors of human ELOVL1. Graphical abstract: Image 1 Highlights: Theoretical model of human ELOVL1 shows a unique opening near the upper occluded end. Modeling of ELOVL1- C26:0-CoA complex suggests that the tail of C26:0 protrudes from the unique opening. Protrusion of C26:0 tail was maintained during 100 ns MD simulation. Previously reported potent and selective ELOVL1 inhibitors (compound 22 and compound 27) bind to the unique opening.